SYSTEMIC LUPUS ERYTHEMATOSUS PRESENTING AS FEVER OF UNKNOWN ORIGIN IN PREGNANCY: A CASE REPORT - Aiysha Gul; Axelle Mayode Atchade; Hiba manzoor; Fath Elrahman Elrasheed; Rizwanullah; Isameldin Elamin Medani; Sudha K Rajan (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that primarily affects women of reproductive age. Pregnancy in women with SLE is often complicated by disease flares, posing significant maternal and fetal risks, such as preeclampsia, lupus nephritis, miscarriage, preterm birth, and intrauterine growth restriction. Diagnosing SLE during pregnancy is particularly challenging due to overlapping symptoms with pregnancy-related conditions. Literature on new-onset SLE in pregnancy is limited, highlighting the need for more case reports to improve understanding and management. We report the case of a 28-year-old primigravida, presenting at 29 weeks of gestation with fever, pancytopenia, and fatigue. Initial investigations ruled out infectious causes, and subsequent autoimmune testing confirmed new-onset SLE. Prompt treatment with corticosteroids and immunosuppressants resulted in the patient’s recovery and successful delivery at 39 weeks without complications. This case underscores the diagnostic challenges of SLE during pregnancy and emphasizes the importance of early recognition and a multidisciplinary approach to management to prevent adverse maternal and fetal outcomes.